Malewska w archiwum. Praktyki pisarskie i obrazy literackie - NOWAK, Maciej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The main theme of the article is the linkages between Hanna Malewska’s biography and her works. The linkages in question are examined with recourse to the French tradition of the research of autobiography, in particular to the notion of autobiographical space developed by Philippe Lejeune. Yet the focus of the present considerations is the concept of the experience of the archives which the author conceives of as a biographical fact which shaped Malewska’s literary output to a significant extent. The particular manifestations of this experience in her biography, described by the author as «traces», are present in various ways and on various planes throughout the writer’s works. While reconstructing the relevant autobiographical space, the author refers both to Malewska’s selfpresentations and to the interviews she gave, as well as quotes the opinions of those who associated her with the space of the archives and other institutions of that kind, such as libraries, reading-rooms, and the writer’s study. The author points to the rich and meaningful intertextual relations which, due to Malewska’s experience of the archives, turn out crucial to her literary output. The «traces» of the archives are distinguished both in the construction of her novels as such and in the philosophy of history encoded in the literary images she uses, as well as in the particular motifs, repeatedly occurring in her succeeding works, that convey the heritage of the past. The final conclusion of the article, however, does not concern the connection between Malewska’s biography and her work, but rather her genuine axiological project, which is significantly rooted in her experience of the archives. Translated by Dorota Chabrajska